AI and Blockchain-Based Approach for Optimization of Carbon Trading Model in REDD+ Scheme in East Java - Haryono Haryono (West Science Interdisciplinary Studies, 2025)
This study examines a new way of maximizing the carbon trading mechanism under the REDD+ strategy in East Java through a mixture of Artificial Intelligence (AI), Blockchain technology, and Geographic Information System (GIS) analysis. GIS tools were employed in an effort to establish high-priority zones to prioritize REDD+ intervention, with AI algorithms refining deforestation estimation and carbon stock calculation accuracy. Blockchain technology was applied to facilitate the automation of carbon credit transactions with security, transparency, and trust for stakeholders. The results revealed significant improvement in MRV processes with increased efficiency and stakeholder satisfaction. The study demonstrates the potential of integrating advanced technologies for sustainable forest management and climate change mitigation and presents a scalable model for global REDD+ programs.